Smart and multifunctional concrete toward sustainable infrastructures - Han, Baoguo; Zhang, Liqing; Ou, Jinping (Springer, 2017)
This book presents the latest research advances and findings in the field of smart/multifunctional concretes, focusing on the principles, design and fabrication, test and characterization, performance and mechanism, and their applications in infrastructures. It also discusses future challenges in the development and application of smart/multifunctional concretes, providing useful theory, ideas and principles, as well as insights and practical guidance for developing sustainable infrastructures. It is a valuable resource for researchers, scientists and engineers in the field of civil-engineering materials and infrastructures.
Keywords: Concrete.; Concrete construction.; Sustainable construction.; elektronické knihy; electronic books